A report of the level of efficiency of Road Transport Department (RTD) in issuing driving licence to applicant: an empirical study towards the case of flying licences / Hamidah Shahar and Rizliana Che Ramli - Shahar, Hamidah; Che Ramli, Rizliana (Faculty of Business and Management, 2001)
This study examines the level of efficiency of Road Transport Department (RTD) in issuing driving licence to applicants : An empirical study towards the case of flying licences. Besides that, this study is addressed to see what are the consequences to the parties involved regarding the case of flying licence. The objective of this study is to know what is the level of efficiency of RTD and how far and certain party take an action towards this issue. In this study we are using the secondary data as our valuable resources. We seek for the literature review from the newspaper, magazines, and information from the internet online. Here, we also used a method like giving a sample of questionnaire to the 50 peoples who selected to be our potential respondents. it includes the students and lecturers of Mara University of Technology from Alor Gajah campus and also the publics who lived in Alor Gajah. Therefore there are several importance or benefits from this study. It depends on the parties involved. For example in this study the importance of this study to licence holder where this study could open their eyes about the consequences that can occur if they think to take the flying licence. Where as on benefits of the RTD staff, this study will be a good lesson for them because of their silly mistake. If we look from the view point of government, this study will encourage them to be more concerned and alert with the problems such like this. Finally, after all the study done using the Chi-square Test our findings state that there are low performance regarding the efficiency of RTD in issuing driving licence to applicants and most of the respondents blame the RTD management who involved in the case offlying licence.